Antigens of Neisseria gonorrhoeae: Characterization by Gel Filtration, Complement Fixation, and Agar-Gel Diffusion of Antigens of Gonococcal Protoplasm - Danielsson, Dan G. (1969)
With the use of the agar-gel-diffusion and complement-fixation techniques, it was shown that protoplasm from different gonococcal isolates reacted with sera from some humans with a history of gonorrhea but did not react with “normal” human sera. The reactive antigen(s) could be partially separated from the other antigens by passing the gonococcal protoplasm through Sephadex G-200. The antigen(s) reacting in the gel-diffusion and complement-fixation tests appeared in the same fraction. On the basis of Sephadex gel filtration, the molecular weight of this antigen(s) is probably greater than 200,000.